Proceedings of the Seventh ACM on Conference on Data and Application Security and Privacy 2017
DOI: 10.1145/3029806.3029807
|View full text |Cite
|
Sign up to set email alerts
|

Secure Free-Floating Car Sharing for Offline Cars

Abstract: Free-floating car-sharing has been one of the latest innovations in the car-sharing market. It allows its customers to locate available vehicles via a smartphone app and reserve them for a short time prior to their rental. Because it is available for point-to-point trips, free-floating car-sharing is not only an alternative to private cars, but also to public transportation. Using spatial regression and conditional logit analysis of original transaction data of a free-floating car-sharing scheme in Switzerland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The current authentication method that allows for starting and using the vehicle is still an immobilizer key [45,46]. The MFA may significantly improve access to most of the electronic devices from both security and user experience perspectives [47,48].…”
Section: Mul�-factor Authen�ca�onmentioning
confidence: 99%
“…The current authentication method that allows for starting and using the vehicle is still an immobilizer key [45,46]. The MFA may significantly improve access to most of the electronic devices from both security and user experience perspectives [47,48].…”
Section: Mul�-factor Authen�ca�onmentioning
confidence: 99%
“…Finally, it verifies the identity of u c . For the last verification, as the OBU receives Cert uc (along with the hash(Cert uc ) in M B ), it can use any challenge-response protocol based on public/private key [19] and RFIDs [20]. If any of these verifications fails, the OBU terminates the car access process and denies access to the car.…”
Section: Sepcarmentioning
confidence: 99%
“…Statistics have shown that the worldwide number of users for car sharing services has grown from 2012 to 2014 by 170% (4.94 million) [1,18,20] with a tendency to increase by 2021 [9]. With the use of portable devices and in-vehicle telematics, physical car keys are slowly becoming obsolete.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations